Catching Small Balls By Modifying The Traditional Boi Game Based On Cooperative Learning For Grade V Students Of MIS Al-Hidayah Cinta Karya - Sayyidi Umar Maulayya Pasaribu; Joko Priono; Imanuddin Siregar (Journal Physical Health Recreation (JPHR), 2025)
This study aims to improve the learning outcomes of throwing and catching small balls by modifying the traditional Boi game based on cooperative learning for grade V students of MIS Al-Hidayah Cinta Karya. This research employs the Classroom Action Research (CAR) method, consisting of two cycles. Each cycle involves planning, implementation, observation, and reflection stages. The results of the study indicate an improvement in learning outcomes from cycle I to cycle II. In cycle I, 15 students (57.69%) achieved learning mastery with an average score of 73.50%. In cycle II, learning mastery increased to 23 students (88.64%) with an average score of 80.76%. These results show that modifying the traditional Boi game can enhance the learning outcomes of throwing and catching small balls.